Contribution for the characterisation of Carolino rice cultivars - Santos, Tania (2013)
Rice is consumed mainly as whole grain, and quality considerations are much more important than for any other food crop. Rice grain quality preference varies from country to country and among regions. Most of the rice produced in Portugal is of the Carolino type, botanically classified as Oryza sativa ssp. Japonica. Nowadays, this rice is playing a vital role in Portuguese rice trading. Thirteen types of Carolino rice were collected and analysed for biometry characteristics, amylose content and gelatinization properties. The Carolino rices are commercially classified as long grains type-A, because they present a length higher than 6 mm and the ratio length/width lower than 3 mm), and there was observed a high variability in biometric measurements. This type of rice showed a high level of plastered area, meaning low vitrea aspect. The amylose content varied from 9.4% and 15.2%, with an average of 12.4%, meaning that Carolino rice presented low value, i.e. that the rice with low amylose content is dry, less tender and hard after cooking, also showing volume expansion and a high degree of flakiness. Carolino rice flours showed significant differences of RVA viscosity profiles. Generally they presented significant differences in the pasting temperature, but similar pasting peak temperature, 95ºC. It was also observed that the different types of Carolino rice flours showed high viscosities (minimum of 2872 cP and maximum 3797 cP), as well as great differences in breakdown and setback values.